Determinasi Kesiapan Kerja Mahasiswa FEB Universitas YPPI Rembang - Ahmad Hamim Djazuli; Susanti Dwi Ilhami (LPPM Politeknik Pratama, 2026)
This study aims to analyze the influence of internship programs, self-efficacy, and academic achievement on students’ work readiness, as well as the correlation among these three independent variables. The study population consisted of 105 students, and a saturated sampling method was used. Data collection was conducted by distributing questionnaires directly to the respondents. Data analysis was performed using multiple linear regression analysis conducted with the data processing application IBM SPSS Statistics version 25. The results of the study indicate that the variables of internship programs, self-efficacy, and academic achievement have a significant positive effect on students’ work readiness. The coefficient of determination was 82.5%, while the remaining 17.5% is explained by other factors outside the model.